High-altitude-induced alterations in intestinal microbiota - Liu, Dan; Chen, Dan; Xiao, Jian; Wang, Wei; Zhang, Li-Juan; Peng, Hui; Han, Chuan; Yao, Hao (Frontiers in Microbiology, 2024)
In high-altitude environments characterized by low pressure and oxygen levels, the intestinal microbiota undergoes significant alterations. Whether individuals are subjected to prolonged exposure or acute altitude changes, these conditions lead to shifts in both the diversity and abundance of intestinal microbiota, as well as changes in their composition. While these alterations represent adaptations to high-altitude conditions, they may also pose health risks through certain mechanisms. Changes in the intestinal microbiota induced by high altitudes can compromise the integrity of the intestinal mucosal barrier, resulting in gastrointestinal dysfunction and an increased susceptibility to Acute Mountain Sickness(AMS). Moreover, alterations in the intestinal microbiota have been implicated in the induction or exacerbation of chronic heart failure. Targeted modulation of the intestinal microbiota holds promise in mitigating high-altitude-related cardiac damage. Dietary interventions, such as adopting a high-carbohydrate, high-fiber, low-protein, and low-fat diet, can help regulate the effects of intestinal microbiota and their metabolic byproducts on intestinal health. Additionally, supplementation with probiotics, either through dietary sources or medications, offers a means of modulating the composition of the intestinal microbiota. These interventions may offer beneficial effects in preventing and alleviating AMS following acute exposure to high altitudes.